Dychotomia rachunkowości - Szydełko, Alfred (Dichotomy of Accountancy, 2005)
The idea of the nature of accountancy, in spite of many existing definitions, seems not to be fully explained. In most publications on this subject, when defining accountancy, elements of its binary division: theory and practice, are not considered. Such an approach unusually reduces the contents contained in the idea of accountancy. This paper, considering the existing ideas, attempts to present fully the nature of accountancy, clearly separating its dichotomous division into practice and theory. In that context ideas about practice of accountancy, treated as a system of recording and a system of providing with information, have been characterized and systematized. The paper also presents the field of accountancy research as a science, as well as the types of enunciations which are used by it, with special attention to mutual dependence and conditioning between the general theory of accountancy and the detailed accountancy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 319-325